Improving Student’s Reading Comprehension Through LRD (Listen–Read– Discussion) Strategy at the Eighth Grade of MTS At-Taqwa Jambi - Fajrudiansyah, Bayu; Dewi, Merry Prima; Safitri, Loli; Syahrul, Syahrul (Education Achievement: Journal of Science and Research, 2024)
This research was done to improve students’ reading comprehension through LRD (Listen-Read-Discussion) strategy. The background of this research was the eighth grade students of MTS At-Taqwa Jambi had the problem in reading comprehension including students reading comprehension was low, students were difficult to find the elements of reading and it was difficult for students to determine the main idea of the text. Furthermore, this research aimed to find out whether there was an improvement in students’ reading comprehension through LRD (Listen-Read-Discussion) strategy at among the eighth - grade students of MTS At-Taqwa Jambi. This research was a classroom action research (CAR). This classroom action research divided into two cycles that referred to the classroom action research procedures were planning, implementing of action, observing, and reflecting. The research data were collected through observation checklist and tests. The test was given to the students in form of a reading comprehension post-test at the end of learning at each cycle. The subject of this research was the eighth grade students of MTS At-Taqwa Jambi. The total number of students in the class was 22 students. The result of the analysis showed that the LRD (Listen-Read-Discussion) strategy could improve students reading comprehension. The result of students reading comprehension test was showed in two cycles. The result showed that there were improvements in students’ reading comprehension scores and reading activity through LRD (Listen-Read-Discussion) strategy. The result obtained by students in the cycle I the average score of the class was 58,52. In the cycle II results obtained by students the average score of the class was 75,57, also students were not difficult in finding the elements of reading in the text and more focused in reading the material in “Read” section. Based on the students’ results in cycle I and cycle II could be concluded that the minimum criteria for score was reached. The minimum criteria for the score (KKM) was 75. Furthermore, it could be conclude that the use of LRD (Listen-Read-Discussion) strategy  could improve students’ reading comprehension.